Population Change and Urban Expansion in the Villages of Bashiqa and Bahzani for the Period 2010-2022 - Hussein, Wissam Abdullah (Journal of Tikrit University for Humanities, 2023)
The research aims to reveal the change in the size and growth of the population in the Bashiqa and Bahzani reeds during the period 2010-2022, and its impact on the expansion on the neighboring agricultural lands, through the creation of non-morphological residential neighborhoods in both districts. The population increase resulting from natural growth and net migration was one of the factors positively affecting the increase in the size of the population of the two districts and their urban changes is through the expansion of its urban structure, which was associated with a positive relationship with the population. In order to reach the best ways to reveal the impact of population change on the expansion of the two districts, this study came to show the presence of continued expansion and population growth during the study period, as their built-up area reached 4.7 square kilometers for the year 2010, then this area increased to record 6.1 km 2 for the year 2022, and the population growth rate reached 2.6% for the same period, and this requires preparing planning for it in order to ensure its balanced growth and work on comprehensive development plans for the infrastructure, and the results of the study showed that the District Municipality Directorate in Bashiqa contributed a major role in the new neighborhoods by providing requirements The main life through the planning of the main and secondary streets as well as the extension of networks for drinking water and sanitation, and the study recommends the need to work on the new master plan of the two reeds to accommodate the expansions in urban land uses while adhering to the laws and regulations that prevent encroachment on the agricultural lands surrounding the city.